2011
DOI: 10.1185/03007995.2011.585396
|View full text |Cite
|
Sign up to set email alerts
|

Impact of weight gain on outcomes in type 2 diabetes

Abstract: Weight management should be an integral part of a T2DM treatment strategy that includes selecting oral antidiabetes medications and insulin products that are weight beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 62 publications
4
58
1
Order By: Relevance
“…We used a more comprehensive approach of subgrouping studies based on behavioural interventions such diet, exercise and lifestyle changes to better reflect the evidence in the current literature. In addition to a modest reduction observed for measures of adiposity such as weight in kilograms, BMI and waist circumference, our review also found associated reductions in intermediate physiological outcomes such as blood pressure and incidence of type 2 diabetes, which reinforces the findings of other systematic reviews 87,88,89 documenting reduction in the need for pharmacologic therapy for blood pressure and glycemic control as a potential clinical benefit of modest weight loss.…”
Section: Comparison With Other Studiessupporting
confidence: 84%
“…We used a more comprehensive approach of subgrouping studies based on behavioural interventions such diet, exercise and lifestyle changes to better reflect the evidence in the current literature. In addition to a modest reduction observed for measures of adiposity such as weight in kilograms, BMI and waist circumference, our review also found associated reductions in intermediate physiological outcomes such as blood pressure and incidence of type 2 diabetes, which reinforces the findings of other systematic reviews 87,88,89 documenting reduction in the need for pharmacologic therapy for blood pressure and glycemic control as a potential clinical benefit of modest weight loss.…”
Section: Comparison With Other Studiessupporting
confidence: 84%
“…Patients were glycemic control, blood pressure, and lipid outcomes in patients with T2DM. [6][7][8][9] As a result, weight management has become increasingly important in patients with T2DM. [10][11][12] Because of the high costs of care and risk of complications that negatively impact quality of life, T2DM is often a top priority for population management within managed care organizations and for providers.…”
Section: Self-reported Adherencementioning
confidence: 99%
“…In most cases, T2DM is associated with overweight or obesity 4 so that weight management may be an essential factor when selecting an appropriate antidiabetic therapy in T2DM 54 . Except metformin, traditional pharmacotherapies for T2DM (insulin, sulfonylureas, glinides, glitazones) can further increase body weight, making management of overweight or obese patients with T2DM quite challenging 4,55 .…”
Section: Body Weightmentioning
confidence: 99%